2015
DOI: 10.3389/fpsyt.2015.00049
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Hormones, Lipids, and Immune Mediators in Post-Traumatic Stress Disorder – A 3-Month Follow-Up Study

Abstract: A number of peripheral blood analytes have been proposed as potential biomarkers of post-traumatic stress disorder (PTSD). Few studies have investigated whether observed changes in biomarkers persist over time. The aim of this study was to investigate the association of combat-related chronic PTSD with a wide array of putative PTSD biomarkers and to determine reliability of the measurements, i.e., correlations over time. Croatian combat veterans with chronic PTSD (n = 69) and age-matched healthy controls (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 94 publications
(105 reference statements)
1
33
3
Order By: Relevance
“…This suggests that TNFcould potentially serve as a state marker of PTSD, given the changes in concentrations observed in response to different interventions. An additional longitudinal study found no difference in TNF-concentrations between baseline assessment and after 3 months of treatment-asusual (Jergovi et al 2015). However, in this study TNF-were not detected in a high percentage of participants, so conclusions cannot be drawn.…”
Section: Tnf-in Human Studies Of Ptsdcontrasting
confidence: 43%
See 2 more Smart Citations
“…This suggests that TNFcould potentially serve as a state marker of PTSD, given the changes in concentrations observed in response to different interventions. An additional longitudinal study found no difference in TNF-concentrations between baseline assessment and after 3 months of treatment-asusual (Jergovi et al 2015). However, in this study TNF-were not detected in a high percentage of participants, so conclusions cannot be drawn.…”
Section: Tnf-in Human Studies Of Ptsdcontrasting
confidence: 43%
“…Only one study demonstrated a loss of their initial statistical significance when including covariates in the analyses (von Känel et al 2007). It is of note that in two of the remaining studies that found no difference in TNF-concentrations between groups, TNF-was not detectable in a high percentage of participants (Gola et al 2013, Jergovi et al 2015, which may account for their findings. The results of invitro investigations of TNF-in PTSD were generally inconsistent.…”
Section: Tnf-in Human Studies Of Ptsdmentioning
confidence: 69%
See 1 more Smart Citation
“…This same discrepancy in the literature also surrounds alterations in anti-inflammatory cytokines in individuals with PTSD (Table 1, B). In some studies, concentrations of IL-8 (Jergovic et al, 2015;Song et al, 2007b) and IL-4 von Kanel et al, 2007) are lower in individuals with PTSD. IL-4 concentrations have also been correlated negatively with total hyperarousal symptoms (von Kanel et al, 2007).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…These theories arise from the studies that indicate that alterations in the hypothalamic pituitary-adrenal axis and increased levels of the glucocorticoid hormone cortisol and pro inflammatory and antiinflammatory cytokines contribute to the neurogenesis of various anxiety disorders. The precise basis of these assumptions is unclear, but prevailing findings show that individuals with PTSD and other anxiety disorders are more likely to have medical conditions associated with prolonged immunosuppression, such as rheumatoid arthritis, irritable bowel syndrome, and cardiovascular disease 8,9 . Genetic predisposition contributes to anxiety disorders.…”
mentioning
confidence: 99%